Political Contents Found in Verbal and Visual Signs of Tempo Magazine Covers - I Putu Aris Sucipta; Desak Putu Eka Pratiwi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research aims to analyze how Tempo magazine uses verbal and visual signs on its covers to construct political narratives and shape public discourse related to the current political situation. Using semiotic analysis, the study examines the way Tempo magazine uses a combination of verbal and visual elements to convey complex political narratives. Two specific covers, “Cawe-Cawe Setelah Pencoblosan” and “Saling Kunci Kursi Menteri,” are analyzed to uncover the implicit messages and socio-political contexts represent. Qualitative methods are applied in this research. The research fr is based on Chandler's (2007) theory of signs, Barthes' (1968) concepts of connotation and denotation, and Cerrato's (2012) color analysis framework. The results indicate the selected magazine covers contain 22 verbal signs and 17 visual signs. Both covers use striking visuals and provocative text to illustrate complex political narratives and make power struggles clearer. Tempo effectively blends cultural language and visual metaphors to simplify these dynamics, highlighting the need for media literacy to understand such messages. The findings highlight how Tempo strategically employs strong imagery and provocative headlines to frame political events, thereby influencing public perceptions and contributing to the construction of political discourse in Indonesia. The conclusion emphasizes that media, through such visual and verbal strategies, not only reflects but actively shapes political realities, underscoring the significant role of the press in guiding public opinion and shaping socio-political narratives. These insights suggest a broader implication for the media’s role in both informing and influencing the political landscape in Indonesia.